2009
DOI: 10.4103/0970-9290.59460
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of a herbal-based toothpaste in the control of plaque and gingivitis: A clinico-biochemical study

Abstract: It was however concluded that the herbal-based toothpaste was as effective as the conventionally formulated dentifrice in the control of plaque and gingivitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 1 publication
5
52
0
2
Order By: Relevance
“…This finding is supported by the study done by George et al, [25] wherein, Colgate herbal toothpaste was as effective as the conventionally formulated dentifrices in the control of plaque and gingivitis. On the contrary, a study by Peck MT et al, [14] stated that Colgate herbal produced inhibitory zones that were significantly smaller than other tested toothpastes (Aquafresh ® Herbal and Dentazyme ® Herbal) except for Nature fresh.…”
Section: Discussionsupporting
confidence: 80%
“…This finding is supported by the study done by George et al, [25] wherein, Colgate herbal toothpaste was as effective as the conventionally formulated dentifrices in the control of plaque and gingivitis. On the contrary, a study by Peck MT et al, [14] stated that Colgate herbal produced inhibitory zones that were significantly smaller than other tested toothpastes (Aquafresh ® Herbal and Dentazyme ® Herbal) except for Nature fresh.…”
Section: Discussionsupporting
confidence: 80%
“…This findings may be attributed to antimicrobial activity resulting from the presence of secondary metabolites such alkaloids, flavonoids, polyphenols and lectins and anti-inflammatory action of herbal extracts. These findings are supported by George J et al (2009) 29 who established in a double blinded controlled clinical trial that the herbal-based toothpaste was as effective as the conventionally formulated triclosan containing dentifrice in the control of plaque and gingivitis.…”
Section: Discussionsupporting
confidence: 64%
“…Laboratory test results showed that the toothpaste can whitens the teeth, kills germs and imparts freshness feel inside mouth. Natural toothpastes and plant extracts also showed significant results to cure various diseases of teeth like gingivitis, 41,42 tooth decay, 43 cavity, 44 gum bleeding, 45,46 bad breath 47 and dental-caries 48 as well as anti-cancerous properties. The present study reported the efficacy of herbal toothpaste in reducing oral bacterial flora, which is also evident by several studies.…”
Section: Antibacterial Efficacy Of Toothpastementioning
confidence: 99%